The Need Of Muslim Floating Market for Bank Syariah: A Case Study of the Member of Pengajian Bisnis al-Kautsar NU in Special District of Yogyakarta - M. Roem Syibly (Millah: Journal of Religious Studies, 2008)
Entrepreneurs of NU, engaged in the al-Kautsar religious gathering, can be deemed as having good education and structural position either as a member or an organizer. They declare that NU institutionally gives a big contribution to their business. Their companies are generally home-industries in which they themselves pay the capital. Though the profit is less than IDR 5,000,000, they are aware of developing their industries. Their participation in the Islamic organization, NU, does not mean that they do not choose the conventional banking system, not the shariah one. Their choice is based upon a consideration which banking system is more beneficial for them. To put simply, it can be said that they will be enthusiastic and interested in utilizing the services of shariah-banking system if they could get more benefits. However, they prefer interest system than profit-sharing system. They consider both systems as being at the same position and regard interest as religiously acceptable. Therefore, they believe that conventional banking system is allowed in Islam. Though having preference to conventional banking system, they still possibly utilize shariah-banking system as long as it can give more facilities and benefits and confess that shariah-banking system is in line with their religious doctrines.Keywords: floating market, entrepreneur of NU, syariah bank.